2015
DOI: 10.1016/j.pec.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Computer use in primary care and patient-physician communication

Abstract: Consultation support can represent a challenge to physicians who recognize its negative impact in patient centered orientation. Medical education programs aiming to enhance specific communication skills and to better integrate computer use in primary care settings are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 49 publications
1
20
0
2
Order By: Relevance
“…As found in other studies, patient satisfaction remained high with physician EHR usage. However, we found that physicians' perceptions vary more, a dichotomy also noted by Gadd and Penrod 1 and Sobral et al 6 Our findings show that, compared with patients, more physicians perceive a negative impact of EHRs on the patient-physician relationship, though the difference between patient and physician perceptions is not as large as the findings of Gadd and Penrod. 1 Other studies have documented the association or lack of association between physician perceptions of EHRs and various physician attributes.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…As found in other studies, patient satisfaction remained high with physician EHR usage. However, we found that physicians' perceptions vary more, a dichotomy also noted by Gadd and Penrod 1 and Sobral et al 6 Our findings show that, compared with patients, more physicians perceive a negative impact of EHRs on the patient-physician relationship, though the difference between patient and physician perceptions is not as large as the findings of Gadd and Penrod. 1 Other studies have documented the association or lack of association between physician perceptions of EHRs and various physician attributes.…”
Section: Discussionsupporting
confidence: 63%
“…1,2,5 Physicians have reported a negative effect of EHRs on their ability to maintain eye contact with patients and their ability to actively listen to patients. 6 Additionally, physicians looking at an EHR during the clinical encounter may appear distracted or disinterested, potentially impacting the patient's perceptions of the physician. 7 Despite these initial negative perceptions of EHR implementation, research reveals improved efficiency in hospitals and outpatient clinics, 2 clinician acceptance and approval of the EHR systems, 2,5,8 and overall patient satisfaction 1,2,[8][9][10][11][12][13][14] with EHR use.…”
mentioning
confidence: 99%
“…Interaction between the nurse and computer commonly seen in general practice adds complexity to the GPN–patient relationship (James et al, 2020). While decreases in nurse–computer eye contact time during the consultation were not significant, previous research indicates that clinicians perceive computer use as having a negative impact on patient‐centred communication (Sobral, Rosenbaum, & Figueiredo‐Braga, 2015). Our findings may be related to the prioritisation of other actions undertaken by the GPN during CDM consultations and between analysis time points.…”
Section: Discussionmentioning
confidence: 63%
“…This is somewhat puzzling because a large number of studies have reported on the effect of aspects of the interior of consultation rooms (or even of adjacent waiting areas) on patient stress and patient disclosure (Okken, van Rompay, and Pruyn 2013;Huisman et al 2012;Ajiboye et al 2015;Miwa 2006;Liu et al 2014;Dahlgaard et al 2008;Sobral, Rosenbaum, and Figueiredo-Braga 2015;Charise et al 2011;Baskaya 2004;Noordman et al 2010;Frankel et al 2005;Almquist et al 2009). For example, Okken et al (2013) found that brightness of the consultation room might influence the communication between the healthcare professional and patient.…”
Section: Current Interventions To Improve Sdmmentioning
confidence: 99%